PERFORMANCE STUDY OF FOAM CONCRETE AS A SUBBASE MATERIAL ON RIGID PAVEMENT - Arditama Harnedi, Raihan
Rigid pavement is a type of pavement that uses a mixture of reinforced concrete as the primary material in its surface layer. This pavement has advantages in terms of strength and service life compared to other types of pavement. One of the factors that can reduce the performance of rigid pavements is a weak subgrade layer. Construction of rigid pavements on weak subgrades can trigger excessive subsidence and may cause damage in the form of cracks or displacement of the joints in the rigid pavement slabs. The solution proposed in this study is to look for alternative materials in the subbase layer to reduce the load received by the subgrade due to the rigid pavement layer system. The alternative material being studied is foam concrete. Foam concrete consists of a mixture of cement, fine aggregate and water, forming mortar and then adding to foam. Foam concrete has the advantage of being a lightweight material with high workability. It is believed that the application of foam concrete not only reduces the load generated by the rigid pavement layer system but also reduces the need for a thick surface layer of concrete from the pavement. This study aims to analyze, evaluate and compare the performance of foam concrete as an alternative material for subbase layers with granular materials for variations in the bearing capacity of subgrade soils. This study examined the mechanical properties of foam concrete at several variations of mixed density, which are 0.6, 0.8, 1.0, 1.2, and 1.4 g/ cm3. The mechanical properties of foam concrete tested are compressive strength, flexural strength, and elastic modulus. The property test results show that the mechanical property of foam concrete is affected by its density with a directly proportional relationship. Based on the results of mechanical property testing, the optimum density of foam concrete used for further analysis is foam concrete with a density of 0.8 g/cm3 because this variation is a mixture with the lowest density and meets the minimum compressive strength value requirements as a subbase layer. Foam concrete samples with optimum density were further analyzed numerically using LUSAS V.19 software to review the stress distribution received by the foam concrete. The analysis shows foam concrete as a homogeneous mixture can spread the load properly and evenly. iv Rigid pavement’s performance analysis begins with the pavement surface thickness design according to AASHTO 1993. Rigid pavements with foam concrete subbase require a thinner surface layer and can carry more load repetitions than conventional rigid pavements. Subgrade on rigid pavements with foam concrete subbase also experience lower and slower rate of consolidation. In addition, the application of foam concrete on a rigid pavement subbase requires lower material costs per vehicle axle than conventional rigid pavements, even though the material costs per volume are almost the same. This can happen because foam concrete has a lower density and higher stiffness than granular material so that a rigid pavement designed using a subbase of this material will be lighter, stiffer, and have a longer design life. Thus, it can be concluded that foam concrete has good performance in terms of its mechanical properties and can be suggested as an alternative material for subbase layers on rigid pavements.